INCLUSIVE GOVERNANCE DALAM KETENAGAKERJAAN DI KOTA PEKANBARU TAHUN 2023-2024 - Rizky Ayu Ramadhani; Rico Purnawandi Pane (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
This research is motivated by the persistently high level of open unemployment in Pekanbaru City, unequal access to employment information, and the low level of involvement of vulnerable groups, particularly people with disabilities, in obtaining employment opportunities. This study aims to describe and analyze inclusive governance in employment in Pekanbaru City in 2023-2024 using the Inclusive Governance theory according to the United Nations Development Programme (2007), which emphasizes three main principles: accessibility and fairness, transparency and accountability, and participation and expanding negotiation space. This study uses a qualitative approach with a descriptive research type. Data collection techniques are carried out through interviews, observation, and documentation. Informants in this study consist of the Pekanbaru City Manpower Office, job seekers, and people with disabilities. The data analysis techniques used include data reduction, data presentation, and conclusion drawing. Data analysis was conducted descriptively to systematically describe the implementation of inclusive governance in employment in Pekanbaru City. The results of the study indicate that inclusive governance in employment in Pekanbaru City has been implemented, but has not been fully optimized substantively and still requires strengthening to realize employment governance that is truly inclusive, fair, transparent, accountable, and participatory. In terms of accessibility and fairness, the government has attempted to provide equal opportunities for the community, but there are still limitations in the provision of disability-friendly facilities. In terms of transparency and accountability, information on employment services has been conveyed through various media, although it is not yet fully inclusive for vulnerable groups. Meanwhile, in terms of participation and expanding negotiation space, community involvement has been carried out, but participation by vulnerable groups is still limited to the consultative stage. Thus, it can be concluded that the implementation of inclusive governance in the employment sector in Pekanbaru City has been carried out normatively and procedurally, but has not yet fully achieved the level of inclusivity substantively. Keywords: Inclusive Governance, Employment, Pekanbaru City